Serum Levels of Zinc, Copper, Vitamin B12, Folate and Immunoglobulins in Individuals with Giardiasis - M Zarebavani; D Dargahi; N Einollahi; N Dashti; M Mohebali; M Rezaeian (Tehran University of Medical Sciences, 2012)
Background: Giardia lamblia is one of the most important intestinal parasites. The aim of this study was to measure serum levels of IgA, IgE, zinc, copper, vitamin B12 and folate in individuals with giardiasis in comparison to normal subjects.Methods: The study was carried out among 49 Giardia positive and 39 age and sex matched healthy volunteers. Examination of stool samples was done by direct wet smear and formol-ether concentration method. Serum samples were obtained for further laboratory examination. IgA levels were measured by Single Radial Immune Diffusion (SRID). IgE levels were measured by ELISA kit. Zinc and copper levels was measured by Ziestchem Diagnostics Kit and colorimetric endpoint-method respectively. Vitamin B12 and folate levels were measured by DRG Diagnostics Kit and Enzyme Immunoassay method respectively. All data were analyzed using SPSS version 17.Results: There was a statistically significant difference in IgA, IgE, copper and zinc levels between positive and negative groups (P<0.05). There was no significant difference between vitamin B12 and folate levels between the two groups. Mean values of Giardia positive and negative groups for IgA were 309.26 and 216.89 mg/dl, IgE 167.34 and 35.49 IU/ml, copper 309.74 and 253.61 µg/dl and zinc 69.41 and 144.75 µg/dl respectively.Conclusion: The results showed levels of IgA may correlate more closely with giardiasis than IgE. Regarding trace elements, giardiasis elevated serum copper levels, while it decreased serum zinc. Finally, there was no significant difference in serum levels of vitamin B12 and folic acid between the two groups.